DEVELOPMENT AND MODELLING OF UNMANNED UNDERWATER GLIDER USING THE SYSTEM IDENTIFICATION METHOD - Mohd Aras, Mohd Shahrieel; Kamarudin, Muhammad Nizam; Jaafar, Hazriq Izzuan; Mohd Nor, Arfah Syahida; Mohd Shah, Hairol Nizam; Anuar , Mohamed Kassim; Ab Rashid, Mohd Zamzuri (MTUN UTeM, 2013)
This paper describes a comparison study for the modelling of the unmanned Underwater Glider (UG) using system identification techniques based on two experimental set up. The experimental data obtained from lab tank test and pool test to infer model using a MATLAB System Identification toolbox. The experimental testing of UG only considered the horizontal movement or called as auto-heading. The modeling obtained will be used to design the suitable controller for heading control. The UG will be tested on an open loop system to obtain measured input-output signals. Input and output signals from the system are recorded and analyzed to infer a model using a System Identification MATLAB toolbox. Two models obtained based on data tabulated and verify using mathematical modelling of UG. The parameter of UG come up from the real model of UG and Solidworks software. The Underwater Lab Tank model has better performance which has faster rise time and settling time than swimming pool model and mathematical model.